Oral cysticercosis - Hercílio Martelli Júnior; Mario Rodrigues Melo Filho; Luis Antônio Nogueira Santos (Universidade Estadual de Campinas, 2015)
Cysticercosis rarely involves the oral region in humans, although is a common disease in developing countries. In this report we document a case of oral cysticercosis in a 7-year-old boy who sought treatment for an asymptomatic nodule of the right buccal mucosa. Histopathologic findings of the excised cyst are diagnostic of the lesion.